Peningkatan Manajemen Keuangan dan Strategi Pemasaran pada Usaha Kecil dan Menengah di Kabupaten Maros - Aini Indrijawati; Darmawati Darmawati; Syamsuddin Syamsuddin; Kartini Kartini; Rahmawati Rahmawati; Ade Ikhlas Amal Alam; Rosnawintang Rosnawintang; Djeza Abrial Iswanto (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
This community service aims to enhance the financial management and marketing strategies of Small and Medium Enterprises (SMEs) in Maros. Many SMEs struggle with financial management, particularly in cash flow management, cost control, and long-term financial planning. Additionally, SMEs face challenges in marketing, especially in digital marketing and product branding. This program provides training on financial management, including the use of spreadsheet software for financial reporting, and digital marketing strategies. The implementation method includes lectures and tutorials, with support materials such as accounting software and instructional guides. The expected outcomes are improved financial management skills, enhanced marketing strategies, and increased business competitiveness. The program will help SMEs manage finances more effectively and expand market reach through better branding and digital strategies.